MENGUKUR KINERJA PENGELOLAAN ZAKAT DI BADAN AMIL ZAKAT NASIONAL (BAZNAS) - DENI LUBIS; DEDI BUDIMAN HAKIM; YUNITA HERMAWATI PUTRI (JEBI (Jurnal Ekonomi dan Bisnis Islam), 2018)
Zakat is one of the Five Pillars of Islam that must fulfilled by all Moslems. The potential of zakat in 2015 was 280 trillion rupiah, but the actual of zakat collected in 2015 were only about 4 trillion rupiah or about 1.4 percent of its potential. This shows that the performance of zakat, both in term of collecting or distributing, were not optimal. The purpose of this research is to evaluate the performance of government and society in managing zakat, the performance of zakat institution, and the effect of zakat towards the welfare of those who have right to receive zakat in Yogyakarta. This research is conducted by using survey method through an interview using questionnaire. The sample is chosen by using purposive sampling technique. The analysis is done by using Indeks Zakat Nasional using Mixed Methods. The result shows that the performance of zakat management in Yogyakarta is quite good with the index value of 0.4338.